Problems of research of the emotional spheare of personality (The Journal of Psychology and Sociology, 2016)
The given article considers the problem of emotional sphere of a personality. The article contains theoretical aspects of emotional sphere of a person, the structure of emotions and methods of diagnosis of emotional state of an individual. It should be noted that researches emotional the condition of the personality is very actual. Discussion of the social nature of emotions is for psychology of one of the most important subjects which demands further evidential development. The social nature of emotion locates through their communication with the world, communication with other people. To emotion the most important part of sincere human life and development of the emotional sphere of the personality it is necessary to pay not less attention, than to development of intelligence, health, physical force and other personal resources. Development of the emotional sphere task actual for everyone. But the direction of this development will be absolutely different depending on type of the personality. In the emotional sphere between the people especially bright individual distinctions are found, in this article foreign socially psychological researches of emotions are considered. Relying on these theoretical and empirical researches the main problems of research of an emotional condition of the personality are allocated. In turn many socially psychological phenomena contain an emotional content. To the main components of emotion refer feeling as conscious experience of emotion and emotional regulation. Researches distinguish emotion as a state and emotion as a personal line. Some emotions covering a number of experiences, is called as emotional episodes. Without studying of the emotional sphere in psychology and social psychology are considered. Key questions of socially psychological studying of the emotional phenomena are discussed. The originality of emotions and feelings is defined by personal properties an orientation of the personality her motives , aspirations, intentions, individual mental properties. The problem of emotional development of the personality is in psychology is one of the most difficult and low studied. Now there is no complete concept of development of the emotional sphere of the personality. Psychology experience and alarm, shyness and stress are considered as one of the main categories characterizing the emotional world of the personality. Changes of the emotional sphere are connected as with physical and a mental condition of the person. In the field of studying of emotional development of the personality, there are still many unsolved questions. All researches note defining value of emotional development in information of the personality. Clarification of its regularities can specify the mechanism of development of the person as a whole as feelings reveal the important parties of an inside world of the person. This article is devoted to studying of problems of the personality and the emotional sphere in psychology. Understanding of the personality as person which are difficult for explaining without this concept. The psychological characteristic of an emotional condition of the person was given. The psychological mechanism and receptions, methods of regulation of emotion was opened.
Keywords: «personality»; «emotions»; «emotional state»; «experience»; «sense»